Global DNA methylation analysis of cancer-associated fibroblasts reveals extensive epigenetic rewiring linked with RUNX1 upregulation in breast cancer stroma - Halperin, Coral; Hey, Joschka; Weichenhan, Dieter; Stein, Yaniv; Mayer, Shimrit; Lutsik, Pavlo; Plass, Christoph; Scherz-Shouval, Ruth (Cancer research, 2022)
Cancer cells recruit and rewire normal fibroblasts in their microenvironment to become protumorigenic cancer-associated fibroblasts (CAF). These CAFs are genomically stable, yet their transcriptional programs are distinct from those of their normal counterparts. Transcriptional regulation plays a major role in this reprogramming, but the extent to which epigenetic modifications of DNA also contribute to the rewiring of CAF transcription is not clear. Here we address this question by dissecting the epigenetic landscape of breast CAFs. Applying tagmentation-based whole-genome bisulfite sequencing in a mouse model of breast cancer, we found that fibroblasts undergo massive DNA methylation changes as they transition into CAFs. Transcriptional and epigenetic analyses revealed RUNX1 as a potential mediator of this process and identified a RUNX1-dependent stromal gene signature. Coculture and mouse models showed that both RUNX1 and its stromal signature are induced as normal fibroblasts transition into CAFs. In breast cancer patients, RUNX1 was upregulated in CAFs, and expression of the RUNX1 signature was associated with poor disease outcome, highlighting the relevance of these findings to human disease. This work presents a comprehensive genome-wide map of DNA methylation in CAFs and reveals a previously unknown facet of the dynamic plasticity of the stroma.The first genome-wide map of DNA methylation in breast cancer-associated fibroblasts unravels a previously unknown facet of the dynamic plasticity of the stroma, with far-reaching therapeutic implications.